The multi PAM2 protein Upa2 functions as novel core component of endosomal mRNA transport. (24th July 2019) - Jankowski, Silke; Pohlmann, Thomas; Baumann, Sebastian; Müntjes, Kira; Devan, Senthil Kumar; Zander, Sabrina; Feldbrügge, Michael
Abstract: mRNA transport determines spatiotemporal protein expression. Transport units are higher‐order ribonucleoprotein complexes containing cargo mRNAs, RNA‐binding proteins and accessory proteins. Endosomal mRNA transport in fungal hyphae belongs to the best‐studied translocation mechanisms. Although several factors are known, additional core components are missing. Here, we describe the 232 kDa protein Upa2 containing multiple PAM2 motifs (poly[A]‐binding protein [Pab1]‐associated motif 2) as a novel core component. Loss of Upa2 disturbs transport of cargo mRNAs and associated Pab1. Upa2 is present on almost all transport endosomes in an mRNA‐dependent manner. Surprisingly, all four PAM2 motifs are dispensable for function during unipolar hyphal growth. Instead, Upa2 harbours a novel N‐terminal effector domain as important functional determinant as well as a C‐terminal GWW motif for specific endosomal localisation. In essence, Upa2 meets all the criteria of a novel core component of endosomal mRNA transport and appears to carry out crucial scaffolding functions. Synopsis: Upa2 acts as scaffolding factor for microtubule‐dependent endosomal mRNA transport. It is present on all shuttling transport endosomes and loss of this core component causes severe defects in mRNA transport. Upa2 contains a uniquely high number of four PAM2 motifs (poly[A]‐binding protein interacting motifs). Upa2 harbors a functionally important novel effector domain at the N‐terminus. Upa2 carries a C‐terminal GWW motif essential for endosomal attachment. Abstract : Upa2 acts as scaffolding factor for microtubule‐dependent endosomal mRNA transport. It is present on all shuttling transport endosomes and loss of this core component causes severe defects in mRNA transport.